Conflicts and Problems in New Word- Formation: A Study on Malaysian Tamil Newspaper - Muniisvaran, K.; Kartheges, P.; Jose, Franklin Thambi; Yuniasanti, Reny (International Journal of Psychosocial Rehabilitation, 2020)
This study is about Tamil language word-formation in Malaysian context. The study gives in-depth findings on two research objectives. The objectives are, to identify the conflicts and problems in newly formed words in Tamil language found in Malaysia newspaper and to provide solutions for the problematic newly formed words in Tamil language. Data for this study were collected from Malaysia Nanban newspaper, a popular daily Tamil newspaper in Malaysia. The study used qualitative method of research and also classified as descriptive study. The main instrument used in this study is the Sura’s Tamil – Tamil – English Dictionary. The findings show that ambiguity in words, forming additional words, forming words for special purpose, inappropriate and unknown meanings for the newly formed words in Tamil language are the problems that identified.